2017
DOI: 10.1039/c7fd90095c
|View full text |Cite
|
Sign up to set email alerts
|

Theory of SERS enhancement: general discussion

Abstract: Rohit Chikkaraddy opened the discussion of the Introductory Lecture: Regarding quantifying the chemical enhancement, you showed a systematic change in the SERS enhancement for halide substituted molecules due to charge transfer from the metal. Is the extra enhancement due to an inherent increase in the Raman cross-section of the molecule? How do you go about referencing, as the charge transfer changes the vibrational frequency? Richard Van Duyne answered: The extra enhancement is not due to an increase in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 2 publications
(3 reference statements)
0
27
0
Order By: Relevance
“…In principle, SERS involves interactions between electromagnetic radiation and molecules adsorbed onto, or in close proximity to, nanoscale rough metallic particles of smaller diameter than the wavelength of excitation radiation [38]. Although there is no comprehensive explanation for the SERS phenomenon to date, and the topic is under active debate [39], the independent research by Van Duyne and Creighton, combined with selection rules of molecules adsorbed on metal surfaces [40], proposed two simultaneously operative theories. The electromagnetic (EM) theory, thought to be the dominant mechanism, is a physical effect which involves optical excitation of electric fields and charge motions created by collective oscillations of electrons in the conduction band (surface plasmon) of NPs.…”
Section: Surface Enhanced Raman Scattering: a Brief Tutorialmentioning
confidence: 99%
“…In principle, SERS involves interactions between electromagnetic radiation and molecules adsorbed onto, or in close proximity to, nanoscale rough metallic particles of smaller diameter than the wavelength of excitation radiation [38]. Although there is no comprehensive explanation for the SERS phenomenon to date, and the topic is under active debate [39], the independent research by Van Duyne and Creighton, combined with selection rules of molecules adsorbed on metal surfaces [40], proposed two simultaneously operative theories. The electromagnetic (EM) theory, thought to be the dominant mechanism, is a physical effect which involves optical excitation of electric fields and charge motions created by collective oscillations of electrons in the conduction band (surface plasmon) of NPs.…”
Section: Surface Enhanced Raman Scattering: a Brief Tutorialmentioning
confidence: 99%
“…7Often, the total enhancement is simplified by the so-called |E| 4 -approximation, which neglects the Raman shift. However, this approximation needs to be treated with caution as many cases have shown [74].…”
Section: (3)mentioning
confidence: 99%
“…This is a non-linear interaction of pump and Stokes laser with the molecules. Recently, P. Dawson et al reported the effects of nonlinear response of metal dielectric constant on the tipenhanced Raman scattering [48][49][50]. In the region around the gap of tip-substrate, the light field is greatly enhanced and a Kerr type non-linearity, locally modified dielectric constant is used to study the Raman scattering.…”
Section: Ultrafast Coherent Control Of Tersmentioning
confidence: 99%